Evaluating The Quality Performance of Sub-Services Provided in Universities from The Students’ point of view (A Field Study on Students of Private Syrian Universities in The Syrian Coast) - حمدان, مهند (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research has aimed to identify the level of quality of services provided in the under study, to know the relative importance of the main and subsidiary dimensions of the quality of service, and to study the relationship between quality and students` satisfaction. The study relied on the approach of the Service Performance, to compare the actual performance of the service provided and the expected performance Of them, The research sample consisted of (317) students from private universities in the Syrian coast (Lattakia and Tartous governorates). The most important results of the research were as follows: It was found that there are significant differences between the dimensions of perceived and expected quality and at the level of all the main dimensions, and these differences were in favor of the expected quality dimensions, meaning that the quality of service meets part of students expectations, and according to the scale of Actual Performance, the most satisfactory dimensions to students are: Responsiveness, Tangibles, Assurance, Reliability, and Sympathy, and there is a significant relationship between quality of services provided and students` satisfaction. The data was analyzed using the statistical analysis program [SPSS V20], using the following set of techniques: Reliability test (Alpha (Cronbach`) - arithmetic mean, standard deviation, frequencies and percentages - Pearson's correlation test - T-test.